Effects of immunosuppression on protection of fry from Ichthyophthirius multifiliis Fouquet 1876 during mouthbrooding of Oreochromis mossambicus (Peters) - Subasinghe, R.P. (Elsevier, 1993)
Members of the family Cichlidae belonging to the genus Oreochromis are maternal mouthbrooders. They protect their eggs and early fry from environmental hazards by keeping fry in their buccal cavities, a confined environment. It has been shown that female Oreochromis mossambicus, effectively immunised against the ciliate ectoparasite Ichthyophthirius multifiliis are capable of protecting their mouthbrooding early fry from subsequent I. multifiliis infections. An investigation was made to study the effects of immunosuppression by injection of the corticosteroid, triamcinolone acetonide, on the protection of mouthbrooding fry from subsequent I. multifiliis infections under oral and artificial incubation. Immunised mothers offered a high level of protection to their early fry against I. multifiliis whilst orally brooded. The protection offered by the immunosuppressed mothers was significantly lower than that of their non-immunosuppressed counterparts. No fry survived following infection with I. multifiliis, under artificial incubation. The mechanism of oral protection with respect to immunity is discussed.